Effects of Rumination and Emotional Regulation on Non-Suicidal Self-Injury Behaviors in Depressed Adolescents in China: A Multicenter Study - He K; Chen L; Fan H; Sun L; Yang T; Liu H; Wang K (Psychology Research and Behavior Management)
Kongliang He,1,2 Lu Chen,1 Hongbin Fan,1 Lingmin Sun,2 Tingting Yang,1 Huanzhong Liu,2,3 Kai Wang2,4 1Psychological Counseling Department, Hefei Fourth People’s Hospital, Hefei, 230022, People’s Republic of China; 2School of Mental Health and Psychological Sciences, Anhui Medical University, Hefei, 230022, People’s Republic of China; 3Department of Psychiatry, Chaohu Hospital of Anhui Medical University, Hefei, 230022, People’s Republic of China; 4Department of Neurology, the First Affiliated Hospital of Anhui Medical University, Hefei, 230022, People’s Republic of ChinaCorrespondence: Huanzhong Liu, Department of Psychiatry, Chaohu Hospital of Anhui Medical University, Hefei, People’s Republic of China, Email huanzhongliu@ahmu.edu.cn Kai Wang, School of Mental Health and Psychological Sciences, Anhui Medical University, Hefei, People’s Republic of China, Email wangkai1964@126.comObjective: Emotion dysregulation is one of the core causes of non-suicidal self-injury (NSSI). However, little is known about the effects of emotion regulation and rumination on NSSI behaviors in adolescents with depressive disorder.Methods: In total, 1782 depressed adolescents (1464 females and 318 males) completed questionnaires on rumination, emotion regulation, and NSSI, with an average age of 14.85. Participants were recruited from the outpatient and inpatient wards of 14 hospitals across the country.Results: NSSI behavior frequency was positively correlated with rumination and negatively correlated with emotion regulation. Cognitive reappraisal and expression inhibition play a significant mediating role in the relationship between rumination and NSSI.Conclusion: Among adolescents with depression, rumination has an impact on the frequency of NSSI behavior, and the relationship between the two is mediated by emotional regulation. The results indicate that intervention with adaptive emotion regulation strategies in adolescent depression patients may reduce the frequency of NSSI, especially in adjusting cognitive evaluation.Keywords: cognitive reappraisal, emotion regulation, NSSI, rumination, response inhibition